Enteral Feeding in Abdominal Compartment Syndrome - Ye. V Grigoryev; Ye. A. Kameneva; S. S. Koval (Общая реаниматология, 2009)
Objective: to substantiate the choice of a gastrointestinal tract (GIT) function support regimen as a mode for correction of the abdominal compartment syndrome (ACS). Subjects and methods. Forty-three patients with different causes of inadequate GIT function of various origin and ACS (disseminated peritonitis (45%), pancreatitis (24%), and severe concomitant injury (31%)) were examined. Group 1 (control) received complete parenteral nutritional feeding (n=23; APACHE II scores, 21±4; calculated probability of fatal outcome, 33.5%). In Group II (study), complete parenteral feeding in the first 24 hours after stabilization was supplemented with GIT function support with Pepsisorb (Nutricia) in doses of 500, 1000, and 1500 ml on days 1, 2, and 3, respectively (n=20; APACHE II scores, 20±6; calculated probability of fatal outcome, 37.1%). During early enteral nutritional support, the SOFA score was significantly less than that in Group 1 on days 2—3; the oxygenation index significantly increased on day 3; the value of intra-abdominal hypertension decreased to the control values. The positive effect of the GIT function support regimen on regression of the multiple organ dysfunction syndrome (MODS) was confirmed by the lowered levels of biological markers (von Willebrand factor (WF) and endothelin-1 as markers of endothelial damage) of MODS. Correlation analysis showed a direct correlation between the markers of endothelial damage and the SOFA scores (r=0.34; p=0.05 for WF and r=0.49;p=0.03 for endothelin). Conclusion. The GIT function support regimen via early enteral alimentation with Peptisorb, which was initiated in the first 24 hours after admission, is able to level off the manifestations of the early stages of the abdominal compartment syndrome, with the acceptable values of oxygen balance and water-electrolyte and osmotic homeostasis being achieved. Key words: abdominal compartment syndrome, nutritional support, biological markers, oxygenation index, intra-abdominal pressure.